The extent to which the Libyan Audit Bureau adheres to the principles of transparency and accountability contained in Standard No. 20 issued by INTOSAI organization: From the auditors' point of view (Journal of Academic Research, 2021)
Accountability and transparency are among the standards issued by the INTOSAI organization that concerns with improving and developing public financial control at international level and aims to promote the work of the higher financial and accounting oversight institutions, including the Libyan Audit Bureau, and so that the Audit Bureau can achieve its goals in preserving public money and limiting the phenomenon of corruption, it must adopt the standards of this organization, including Standard No. (20) that includes the principles of accountability and transparency.       This study aimed to find out the extent of the Libyan Audit Bureau's commitment to the principles of transparency and accountability contained in INTOSAI organization standard No. (20).       In order to achieve the objectives of the study and the answer to its inquiries, the descriptive and analytical approach was used and the data obtained through a questionnaire form with quintuple "Five Likert" scale prepared through the principles of the aforementioned standard No. (20) and distributed to the study community, which is the auditors at the General Administration of the Libyan Audit Bureau in Tripoli of (209), where (140) were retrieved, and the statistical package for social sciences (SPSS) programme was used to conduct the analysis.       The study concluded that the Libyan Audit Bureau adheres to the nine principles of  transparency and  accountability  contained in standard  No. (20) issued by INTOSAI organization.